2010
DOI: 10.1063/1.3486117
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magnetoresistance by hydrogen ion treatment for current-perpendicular-to-plane giant magnetoresistive films with a current-confined-path nano-oxide layer

Abstract: We have enhanced magnetoresistance ͑MR͒ for current-perpendicular-to-plane giantmagnetoresistive ͑CPP-GMR͒ films with a current-confined-path nano-oxide layer ͑CCP-NOL͒. In order to realize higher purity in Cu for CCPs, hydrogen ion treatment ͑HIT͒ was applied as the CuO x reduction process. By applying the HIT process, an MR ratio was increased to 27.4% even in the case of using conventional FeCo magnetic layer, from 13.0% for a reference without the HIT process. Atom probe tomography data confirmed oxygen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In 2010, Yuasa et al [270] of Toshiba reported NOL-based MR ratios ranging from 25% to 27.4%, coupled with ARs ranging from 400 to 4000 fΩm 2 , after using a hydrogen ion treatment (HIT) on a FeCobased EBSV CCP multilayer. To form the NOL, they started with a thin AlCu layer, which they first subjected to IAO to fully oxidize the Al to Al 2 O 3 but leave the Cu less oxidized to give Cu pinholes to form the CCPs.…”
Section: Historymentioning
confidence: 99%
“…In 2010, Yuasa et al [270] of Toshiba reported NOL-based MR ratios ranging from 25% to 27.4%, coupled with ARs ranging from 400 to 4000 fΩm 2 , after using a hydrogen ion treatment (HIT) on a FeCobased EBSV CCP multilayer. To form the NOL, they started with a thin AlCu layer, which they first subjected to IAO to fully oxidize the Al to Al 2 O 3 but leave the Cu less oxidized to give Cu pinholes to form the CCPs.…”
Section: Historymentioning
confidence: 99%
“…Figure 19 [106] compares calculated values of signal-to-noise ratios (SNR) for such a CCP device, with TMR and all metallic CPP-MR devices with plausible assumed values of AR and MR%. Hydrogen ion treatment (HIT) increased the CPP-MR of a CCP-based multilayer to about 25 % for AR $ 500 fOm 2 [114]. To be competitive for devices, both the size and distribution of channels would have to be well controlled in nm-scale pillars, control not yet demonstrated.…”
Section: Current-confined Paths (Ccp) Via Nano-oxide Layers (Nol)mentioning
confidence: 99%
“…It has been reported that a current-confined-path (CCP) structure is useful for improving CPP-GMR. [9][10][11][12] The structure is made of a thin insulator with metallic nano-holes that confine current paths in real space. To attain higher MR ratio, however, CPP-GMR must be further improved.…”
Section: Introductionmentioning
confidence: 99%